P598 The utility of the "Low Anterior Resection Syndrome SCORE" in assessing the postoperative outcomes of patients undergoing restorative proctocolectomy with ileal pouch anal-anastomosis for Ulcerative Colitis. (30th January 2023) - Perotti, S; Mineccia, M; Daperno, M; Massucco, P; Gonella, F; Ferrero, A
Abstract: Background: Restorative proctocolectomy with ileal pouch anal anastomosis (IPAA) in a J-pouch configuration is the treatment of choice for patients with ulcerative colitis. Some patients who have undergone this surgery present symptoms including fecal or gas incontinence, urgency, clustering, and frequency, that occurs after anal sphincter-sparing surgery for the treatment of rectal cancer. There is a lack in standardization and evaluation of functional outcomes. Our aim is to evaluate the effectiveness of the LARS (low anterior resection syndrome) score in this cohort of patients. Methods: We conducted a retrospective analysis of a prospectively maintained single center database. We assessed the quality of life by using the Inflammatory Bowel Disease Questionnaire (IBDQ-32). The functional bowel complaints were assessed using the LARS score. Results: Between 2015 and 2020, 70 patients with ulcerative colitis underwent total colectomy and subsequent IPAA with J-Pouch configuration. Among these, 49 patients who closed the ileostomy and were followed for at least 6 months, were selected for the present study. Nineteen patients did not have the LARS; among 30 who complained the LARS, 17 had a major LARS (tab.1). The latter had a worse quality of life on the IBDQ-32 questionnaire, especially in relation to urgency and frequency (Fig.1). We compared the two scores using Spearman's test correlation coefficient, detecting a significant correlation (rho -0.7664185; p-value <0.005); a significant correlation between the urgency sub-category with LARS score (rho -0.6515759; p-value <0.005) and frequency (rho -0.6744705; p-value <0.005) was evaluated. Tab 1: Patients characteristics: Fig.1:IBDQ-32 value in different LARS categories Conclusion: In our experience LARS score appears to be a useful, effective and simple tool to predict functional outcomes and QoL not only in oncological rectal sphincter-sparing surgery but also in functional surgery for ulcerative colitis.